Accessibility of Persons With Disabilities to Study in Higher Education Institutions - Sukirno Kirno; Nataya Premchaiporn (Yayasan Ilomata, 2022)
The Indonesian government has prohibited universities from refusing students with disabilities to study in universities. This is clearly stated in the Regulation of the Minister of Research and Technology - Higher Education, Number 46 of 2017 concerning Special Education and Special Service Education in Higher Education. But unfortunately, there are still many universities that refuse to accept persons with disabilities to study in their educational institutions. This study is intended to answer the question why universities reject special needs students and what the best solutions are so that special needs students can gain access to study in higher education. This is a qualitative research with a phenomenological approach because it describes a specific, profound phenomenon and obtains the essence of the participants' life experiences at a particular phenomenon. Data was collected through semi-structured interviews with 20 special needs students who graduated from Special Schools who experienced rejection when applying to college. The results of this study indicate that universities need to consider four aspects in managing their programs in order to create inclusiveness in their educational institutions, namely Availability, Accessibility, Acceptability, and Adaptability. In addition, stricter supervision is needed to impose sanctions on universities that reject persons with disabilities.